The oceans and climate - Bigg, Grant R. (Cambridge University Press, 2003)
"This comprehensive textbook on the ocean-climate system will prove an ideal course and reference book for undergraduate and graduate students studying earth and environmental sciences, oceanography, meteorology and climatology. The book will also be useful for students and teachers of geography, physics, chemistry and biology."--Jacket